Understanding Open Access : When, Why & How to Make Your Work Openly Accessible - Rubow, Lexi; Schofield, Brianna; Shen, Rachael (Author's Alliance, 2015)
Understanding Open Access provides a scholarly author-oriented look at the ins and outs of open access publishing. The guide addresses common concerns about what "open access" means, how institutional open access requirements work, and why authors might consider making their work openly accessible online. Our aim is to provide real-life strategies and tools that authors can use to work with publishers, institutions, and funders to make their works available on the terms most consistent with their dissemination goals.